2013
DOI: 10.1177/1759720x12468659
|View full text |Cite
|
Sign up to set email alerts
|

Fibrates as therapy for osteoarthritis and rheumatoid arthritis? A systematic review

Abstract: Fibrates are used as lipid-lowering drugs to prevent cardiovascular pathology. Fibrates are ligands of peroxisome proliferator-activated receptor α (PPARα). Besides altering lipid metabolism, PPARα ligands exert anti-inflammatory effects on various cell types. In this study, we hypothesized that PPARα agonists exert beneficial effects on osteoarthritis (OA) and rheumatoid arthritis (RA) by their local anti-inflammatory effects, but also by their systemic influences. A systematic literature search of Medline an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 55 publications
0
12
0
1
Order By: Relevance
“…[25] The macromolecular network forming breaks up at the cartilage surface in OA. [26] Macromolecules of the cartilage extracellular matrix released into synovial fluid, blood, or urine are useful biomarkers that may contribute to the OA pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…[25] The macromolecular network forming breaks up at the cartilage surface in OA. [26] Macromolecules of the cartilage extracellular matrix released into synovial fluid, blood, or urine are useful biomarkers that may contribute to the OA pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…However, subsequent attempts at replicating these early promising results using other fibrates to alleviate muscular pain have not been successful (Biga et al ., ). Nevertheless, these drugs were found to be effective in attenuating pain associated with rheumatoid arthritis and osteoarthritic pain (van Eekeren et al ., ). These findings indicate that synthetic PPARα agonists can have analgesic effects in specific types of pain.…”
Section: Evidence From Clinical Trialsmentioning
confidence: 99%
“…Experimental studies in vivo and in vitro have shown that PPARα agonists inhibit bone resorption and reduce inflammation, the degradation of the synovial fluid, and the destruction of the articular cartilage. Consequently, PPARα ligands reduce pain, diminish joint tumefaction and determine a decrease in inflammatory markers at systemic level [46].…”
Section: The Role Of Pparα Receptors In Rheumatoid Arthritismentioning
confidence: 99%